2024
DOI: 10.3390/plants13020312
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Expression Profiling Reveals the Molecular Response to Salt Stress in Gossypium anomalum Seedlings

Huan Yu,
Qi Guo,
Wei Ji
et al.

Abstract: Some wild cotton species are remarkably tolerant to salt stress, and hence represent valuable resources for improving salt tolerance of the domesticated allotetraploid species Gossypium hirsutum L. Here, we first detected salt-induced stress changes in physiological and biochemical indexes of G. anomalum, a wild African diploid cotton species. Under 350 mmol/L NaCl treatment, the photosynthetic parameters declined significantly, whereas hydrogen peroxide (H2O2) and malondialdehyde (MDA) contents increased. Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In Pyrus betulifolia , the PbWRKY gene responds to both high temperature and drought stress and exhibits a high expression trend [ 31 ]. The transcriptome of Gossypium anomalum seedlings revealed that the GaWRKY gene is involved in salt stress response, and was validated via qRT-PCR to be consistent with RNA-seq data [ 32 ].…”
Section: Resultsmentioning
confidence: 95%
“…In Pyrus betulifolia , the PbWRKY gene responds to both high temperature and drought stress and exhibits a high expression trend [ 31 ]. The transcriptome of Gossypium anomalum seedlings revealed that the GaWRKY gene is involved in salt stress response, and was validated via qRT-PCR to be consistent with RNA-seq data [ 32 ].…”
Section: Resultsmentioning
confidence: 95%
“…Upregulated RNA-Seq [338,339] 6. Breeding techniques have traditionally been used to produce resilient cotton cultivars.…”
Section: Activation Of Genes Involved In Uv Protectionmentioning
confidence: 99%